¿CÓMO MEDIMOS EL SERVICIO? - Begazo Villanueva, José Domingo (2006)
In selling of products or services, marketing function has an important role verifying the needs and expectatives of the consumers. It is analyzed what the customers require when buying a product or service, their preferences, satisfactions and requirements. Tangiblity of a product goes with the intangibility of the expectatives that must be measured in function of customer’s perceptions. It is all about the current article when analyzing how to measure the intangibility of a commodity, product or service in the market.